Recognition and Reform in Nordic Fiction: Jonas Gardell and Jussi Valtonen. Issue 2 (8th June 2016) - Saarinen, Risto
Abstract: While contemporary Scandinavian literature continues to discuss the problems of welfare state and social justice,  it increasingly turns its attention to minority issues, multiculturalism, and the impact of digitalization. Jonas Gardell's HIV/AIDS trilogy Torka aldrig tårar utan handskar (Never wipe tears without gloves) highlights the family relations in the Swedish gay community. Jussi Valtonen's He eivät tiedä mitä tekevät (They do not know what they do) deals with the dystopias of social media and the power of global software companies. Religion and theology play a significant role in the works of both Gardell and Valtonen.